Encouraging Social Harmony Through Mainstreaming Religious Moderation in Banyumas Regency - Uus Uswatusolihah; Dedy Riyadin Saputro (Alfuad: Jurnal Sosial Keagamaan, 2023)
This article examines the implementation of the Islamic Extension Instructor (Penyuluh Agama Islam/PAI) on religious moderation to encourage social harmony in the Banyumas regency. The PAI is the spokesperson for the Ministry of Religion, which is vital in the success of the religious moderation movement, which deals directly with the community. Banyumas district is considered a district with a high index of harmony and tolerance. This research is qualitative and descriptive, with a phenomenological approach using interviews and document analysis. This study involved 14 PAI who were selected based on a purposive and snowballing sample. The theory that underlies this research is the theory of symbolic interactionism. PAI views and understandings of religious moderation from education, training, and media sources. PAI views Islam as a religion that strongly promotes compassion, tenderness, peace, and tolerance. Islam actually does not need a religious moderation movement because even without a religious moderation movement, Islam is already moderate. These compassionate Islamic values are obscured by the attitudes of some Muslims with extreme views. In general, they understand religious moderation as a religious attitude that is not extreme and upholds tolerance. They encouraged religious moderation according to their ability, situation, and condition. PAI implements religious moderation through actual activities with followers of other religions. This communication strategy for religious moderation among PAI in Banyumas Regency provides an overview of the religious moderation movement at the grassroots.